Age-differentiated Risk Factors of Suicidal Ideation among Young and Middle-aged Korean Adults - Jo, Ahra; Jeon, Minho; Oh, Heeyoung (Osong public health and research perspectives, 2017)
This study aimed to determine the prevalence of suicidal ideation among young and middle-aged adults, and explore the risk factors that affect suicidal ideation. A descriptive study design was used for secondary data analysis. A total sample of 5,214 was drawn from two waves (2012-2013) of the 7th Korea Health Panel (KHP) survey. The KHP data were collected by a well-trained interviewer using the face-to-face method during home visits as well as self-report method. Descriptive statistics of frequency, percentage, chi-square test, and logistic regression analysis were performed using SPSS 22.0. The prevalence of suicidal ideation in young and middle-aged adults was 4.4% and 5.6%, respectively. For young adults, suicidal ideation risk was higher among those with low income or heavy drinking habits. In middle-aged adults, low income, poor perceived health status, negative perception of peer-compared health status, and negative social perspective were the major risk factors. There is considerable risk of suicidal ideation in adulthood. Opportunities for increased income, avoidance of heavy drinking, and the construction of positive subjective health status and social perspective should be considered in suicide prevention interventions for Korean young and middle-aged adults.